Review: Biogas Production from Rice Straw - Sari, Listiyani Nurwindya; Prayitno, Hadi; Farhan, Muhamad; Syaichurrozi, Iqbal (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2022)
Rice straw is a rice plant whose fruit (grain) has been removed, so only the stems and leaves are left. Rice straw is the largest among rice plant waste and has not been utilized as well. Utilization of rice straw waste is not optimal because its usually used for cattle feed and as organic fertilizer. Apart from being used as cattle feed and organic fertilizer, methane gas can still be used for alternative renewable energy sources such as biogas. Rice straw has a carbon-to-nitrogen (C/N) ratio content between 50-70. However, to achieve the optimum biogas formation, the substrate requires a C/N ratio of 20-30, therefore a combination of other waste mixtures, such as cow dung or waste that has a low C/N ratio content is usually carried out.